Brown spot of rice: an overview - and RASHMI AGGARWAL, S. SUNDER, RAM SINGH* (Indian Phytopathology, 2014)
Brown spot of rice caused by Bipolaris oryzae (telemorph=Cochliobolus miyabeanus) is of worldwide occurrence and is known to cause substantial quantitative and qualitative losses in grain yield. The disease is of particular significance under low input management, water stress and direct seeding conditions. The disease is of historical importance in the country. The pathogen has wide host range and exhibits pathogenic and molecular variability. With availability of full genome sequence of its teleomorph, Cochliobolus miyabeanus and other Cochliobolus species, comparative genome analysis can lead to better understanding of host pathogen interaction and disease management. In this article all these aspects are discussed.